Nation-Building as Necessary Effort in Fragile States - Grotenhuis, René (Amsterdam University Press, 2016)
Policies intended to bring stability to fragile states tend to focus almost exclusively on building institutions and systems to get governance right. Simply building the state is often seen as sufficient for making it stable and legitimate. But policies like these, René Grotenhuis shows in this book, ignore the question of what makes people belong to a nation-state, arguing that issues of identity, culture, and religion are crucial to creating the sense of belonging and social cohesion that a stable nation-state requires.